Fiction and Friction on Imaginaries of the Rural World: the Andes in Luis Figueroa’s Los perros hambrientos - Delgado, Mónica (2016)
As opposed to other Peruvian films, where the Andes appear showcased as a transit territory which must be fled, in Los Perros Hambrientos (1976), Cuzquean filmmaker Luis Figueroa shares a view of the mountains and fields as a political place of possibility and resistance against the landowner’s arrogance. While it dramatically differs from the original novel by Ciro Alegría, it also finds in the text the necessary basis to show the moral decadence of the landowner, to abandon the bucolic nostalgia and the animal parable of the text, and submerge itself in the savage dichotomies of rich man / poor man and peasant versus landowner.